A molecular case-control study of the Merkel cell polyomavirus in colon cancer. - Campello, Cesare; Comar, Manola; D'Agaro, Pierlanfranco; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2011)
To explore the putative role of the Merkel cell polyomavirus in human colon cancer, a prospective molecular case-control study was undertaken in patients and their relatives enrolled during a screening program. Fresh tissue samples from 64 cases of colon cancer (mean age 69.9 ± 11.0 years; 40 males) and fresh biopsies from 80 relatives (mean age 53.7 ± 8.6 years; 43 male; 55 son/daughter, 23 brother/sister, 2 parents) were analyzed by PCR and sequencing. Pre-cancerous lesions, namely adenomas and polyps, were detected in 15 (18.8%) and 9 (11.2%) of the controls, respectively. In addition, 144 blood samples were examined. Merkel cell polyomavirus DNA was detected in 6.3% of cases and 8.8% of controls. This difference was not statistically significant in the logistic regression analysis, after adjustment for age. Whereas blood samples from both cases and controls tested negative, the DNA Merkel cell polyomavirus was identified in 12.5% of adenoma/polyp tissues. No statistically significant difference was found when prevalence rates of Merkel cell polyomavirus in normal, pre-cancerous and cancer tissues were compared. Sequence analysis of the viral LT3 and VP1 regions showed high homology (>99%) with those of strains circulating worldwide, especially with genotypes detected in France. The findings of this survey are consistent with the hypothesis that the Merkel cell polyomavirus, in addition to other human polyomaviruses, can be recovered frequently from the gastrointestinal tract, because it is transmitted throughout the fecal-oral route. Moreover, the study does not indicate a role for Merkel cell polyomavirus in the genesis of colon cancer.
Keywords: Aged; Aged, 80 and over; Case-Control Studies; Cluster Analysis; Colonic Neoplasms; DNA, Viral; Female; Genotype; Humans; Italy; Male; Merkel Cells; Middle Aged; Molecular Sequence Data; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Tumor Virus Infections